Antibody-recognizing residues 188-211 of TMEM106B exhibit immunohistochemical reactivity with the TMEM106B C-terminal fragment - Ishikawa, Ruoyi; Yamazaki, Yu; Nakamori, Masahiro; Takahashi, Tetsuya; Maruyama, Hirofumi (Frontiers in Neuroscience, 2023)
Accumulation of TMEM106B fibrils composed of cleaved C-terminal fragments (CTF) of transmembrane protein 106B (TMEM106B) has recently been observed in the brains of elderly subjects and individuals with neurodegenerative diseases. To date, one antibody recognizing the residues 239-250 has been found to display immunoreactivity to the TMEM106B CTF, thereby defining TMEM106B C-terminal immunoreactive (TMEM-ir) material. Immunohistochemical characterization of the CTF using antibodies targeting different immunogens could further shed light on the attributes of TMEM-ir material and the biological relevance of TMEM106B fibril accumulation in vivo. Therefore, we generated and validated five polyclonal antibodies against distinct CTF immunogens, namely the residues 140-163, 164-187, 188-211, 239-250, and 253-274. The antibody recognizing the residues 239-250 (antibody no. 5: 239-250) was employed to identify cases positive for TMEM-ir material. Among the remaining four antibodies, antibody no. 3: 188-211 exhibited significant immunoreactivity in TMEM-ir material-positive cases. Comparative analyzes indicated that antibody no. 3: 188-211 and antibody no. 5: 239-250 likely recognized the same TMEM-ir material. The TMEM-ir material detected by antibody no. 3: 188-211 was observed across multiple brain cell types without co-localization with other pathogenic proteins. In conclusion, our findings suggest that the antibody recognizing the residues 188-211 displays immunohistochemical reactivity to TMEM-ir material. Therefore, in addition to the established antibody recognizing the residues 239-250, the antibody recognizing the residues 188-211 can potentially be used in immunohistochemical studies to further elucidate the significance of CTF accumulation in the brain.